Hibernating squirrel muscle activates the endurance exercise pathway despite prolonged immobilization - Xu, Ran; Fink, Rainer (Experimental neurology, 2013)
Skeletal muscle atrophy is a very common clinical challenge in many disuse conditions. Maintenance of muscle mass is crucial to combat debilitating functional consequences evoked from these clinical conditions. In contrast, hibernation represents a physiological state in which there is natural protection against disuse atrophy despite prolonged periods of immobilization and lack of nutrient intake. Even though peroxisome proliferator-activated receptor γ (PPARγ) coactivator 1-α (PGC-1α) is a central mediator in muscle remodeling pathways, its role in the preservation of skeletal muscle mass during hibernation remains unclear. Since PGC-1α regulates muscle fiber type formation and mitochondrial biogenesis, we analyzed muscles of 13-lined ground squirrels. We find that animals in torpor exhibit a shift to slow-twitch Type I muscle fibers. This switch is accompanied by activation of the PGC-1α-mediated endurance exercise pathway. In addition, we observe increased antioxidant capacity without evidence of oxidative stress, a marked decline in apoptotic susceptibility, and enhanced mitochondrial abundance and metabolism. These results show that activation of the endurance exercise pathway can be achieved in vivo despite prolonged periods of immobilization, and therefore might be an important mechanism for skeletal muscle preservation during hibernation. This PGC-1α regulated pathway may be a potential therapeutic target promoting skeletal muscle homeostasis and oxidative balance to prevent muscle loss in a variety of inherited and acquired neuromuscular disease conditions.